Cultural Identity and Racism (المجلة الدولية للبحوث العلمية, 2023)
This paper delves into the intricate relationship between cultural identity, racism, and the various factors shaping these dynamics, particularly within the context of the United States. Cultural identity is explored as a pivotal aspect of individual and collective existence, profoundly influenced by racial constructs and historical legacies. Racism, deeply embedded in societal structures, is identified as a significant impediment to fostering harmonious cultural relations. This paper emphasizes the critical role played by films, academic works, artworks, and increased cultural diversity in shaping and improving cultural identities. Examining the concept of race, the paper underscores its historical and cultural underpinnings, pointing out its impact on societal divisions and inequalities. Stuart Hall, who promoted Afro-Caribbean cultural identity through cinema, is discussed. Cultural practices, historical events, and film depictions of the Black experience are examined as crucial to cultural identity maintenance and rediscovery. The paper also emphasizes race diversity and Black intellectuals' role in cultural reshaping. Cultural identity is complex, and double consciousness and Black Atlantic diaspora experiences are crucial. Music is especially effective at expressing cultural diaspora and continuity. Jazz and contemporary Black art movements helped shape cultural identity. The paper argues that art, intellectual pursuits, and written history help people feel connected and understand diverse cultures. Despite these positive influences, racism still hinders cultural identity, the paper says. The paper argues that cultural identities must be preserved by avoiding racism and promoting cultural relativity. Lack of cultural integration also erodes cultural identities. The paper concludes by emphasizing cultural identity preservation and recommends a multidisciplinary approach involving media, history, academia, and art for overcoming racism to promote diversity and cultural integration.